Gostar das palavras divinas e do que ali se trata: as celebrações litúrgicas pós tridentinas nos conventos femininos de beneditinas e cistercienses. - Conde, Antónia Fialho (2018)
The present study framed in post-Tridentine contexts and within the monastic experience in the convents of Cistercian and Benedictine nuns, presents word celebration features of the Holy Scriptures in its various forms: sung, read, meditated and prayed. Based on historical sources coming from the female monasteries of the Orders of St. Benedict and Cistercian, both based in St. Benedict Rule, the study is dedicated in particular to the Monastery of S. Bento of Cástris (Évora) and Monasteries of Semide (Coimbra) and S. Salvador (Braga), and presents a reflection of the prayed word, sung word and the rite as a key element of the liturgical celebration.